Developing Order and Queue Web Systems Using User Centered Design in Diskominfo Mojokerto - Ichwan Wahyu Utama; Aries Dwi Indriyanti (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2026)
The management of application development services at the Department of Communication and Informatics (Diskominfo) of Mojokerto Regency is still conducted manually, resulting in queue uncertainty and service delays. This study aims to design and implement an online order and queue management website application using the User-Centered Design (UCD) method. This method involves users at every stage of development, including planning, design, implementation, and evaluation. The application was developed using React JS (front-end), Express JS (back-end), and MySQL (database). Evaluation was conducted through usability testing involving 21 respondents from Regional Government Organizations (OPD) of Mojokerto Regency. The results show an average System Usability Scale (SUS) score of 79.41, exceeding the minimum standard score of 68. This indicates that the application is easy to use, efficient, and aligned with user needs.